2020
DOI: 10.1111/nph.16716
|View full text |Cite
|
Sign up to set email alerts
|

A plant RNA virus activates selective autophagy in a UPR‐dependent manner to promote virus infection

Abstract: Autophagy is an evolutionarily conserved pathway in eukaryotes that delivers unwanted cytoplasmic materials to the lysosome/vacuole for degradation/recycling. Stimulated autophagy emerges as an integral part of plant immunity against intracellular pathogens. In this study, we used turnip mosaic virus (TuMV) as a model to investigate the involvement of autophagy in plant RNA virus infection. The small integral membrane protein 6K2 of TuMV, known as a marker of the virus replication site and an elicitor of the u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
58
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(62 citation statements)
references
References 66 publications
3
58
0
1
Order By: Relevance
“…Therefore, the reasons for the diseases induced by rhythmic autophagy dysfunction are discussed here. Rhythmic autophagy is capable of removing damaged materials from cells regularly, and a deficiency in this process can lead to the accumulation of abnormal cellular components, which finally induce cells and whole organisms to undergo pathological conditions (Li et al, 2020;Wu and Nagy, 2020). Autophagy might be activated to eliminate damaged organelles, proteins and lipids after oxidative phases of metabolism (Pacheco et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the reasons for the diseases induced by rhythmic autophagy dysfunction are discussed here. Rhythmic autophagy is capable of removing damaged materials from cells regularly, and a deficiency in this process can lead to the accumulation of abnormal cellular components, which finally induce cells and whole organisms to undergo pathological conditions (Li et al, 2020;Wu and Nagy, 2020). Autophagy might be activated to eliminate damaged organelles, proteins and lipids after oxidative phases of metabolism (Pacheco et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Cytoplasmic materials are first surrounded by vesicles, which eventually form double membrane structures called autophagosomes (Klionsky et al, 2014;Gou et al, 2020). The autophagosomes then fuse with lysosomes and create autolysosomes where the cargo is degraded and released as critical nutrients, such as fatty acids, back into the cytosol (Gatica et al, 2018;Li et al, 2020;Patra et al, 2020). Autophagy is capable of regulating many0020biochemical processes, including embryogenesis, development, antigen presentation, metabolism and infection removal (Bonam et al, 2020;Farhan et al, 2020;Wu and Nagy, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Targeting TuMV VRCs to tonoplast and promote viral replication and assembly. [110] Hordeivirus BSMV γb NbATG7…”
Section: Pathogens Develop Various Strategies To Counteract the Host mentioning
confidence: 99%
“…It has been reported that Beclin1/ATG6 in N. benthamiana serves as a cargo receptor that selectively mediates the degradation of TuMV NIb protein (RDRP) and restricts TuMV replication [ 98 ]. Interestingly, the same group showed that NBR1 can serve as a selective receptor for TuMV NIb via interacting with ATG8f [ 110 ]. However, instead of being targeted to vacuoles for degradation, the NIb-NBR1-ATG8f-containing autophagosomes, to which the viral replication complexes (VRCs) are associated, are targeted to the tonoplast via an interaction between ATG8f and the tonoplast-intrinsic protein 1 (TIP1), leading to robust viral genome translation/replication and virion assembly in the tonoplast-associated VRCs [ 110 ].…”
Section: Selective Autophagy—a Battlefield Between Plant–pathogen mentioning
confidence: 99%
See 1 more Smart Citation